The Relationship between Organisational Structure and Work Productivity: A Comparative study on the telecom Industry in India - Thundathil Jacob, Koshy (2010)
This study aims to find out the relationship between organisational structure and work productivity which are themselves two core concepts which could be responsible for the holistic growth and progress of an organisation. This study was carried out through qualitative research in three major telecom companies in India by conducting direct interviews to gather relevant information. The three different genre of telecom companies were selected intending to obtain a more reliable and holistic result through the research and the interview was set with the aim to attain answers for the basic research objectives and questions. The study revealed that there exists a complementary and positive relationship between organisational structure and productivity in these telecom companies and the right structure can influence the telecom personnel to improve their work productivity for the total development of the organisation. This research intends to possess clear, relevant and accurate information regarding the topic and has been conducted with utmost care and concentration